Pengaruh Sosialisasi Perpajakan, Sanksi Perpajakan Dan Pengetahuan Perpajakan Terhadap Kepatuhan Wajib Pajak Melalui Kesadaran Wajib Pajak Sebagai Variable Intervening ( Studi Pada Wajib Pajak Kantor Pajak Pratama Klaten ) - Suryo, Dimas Atmoko; Arifin, Atwal (Pascasarjana STIE Amkop Makassar, 2024)
This research aims to analyze tax socialization, tax sanctions and tax knowledge on taxpayer compliance through taxpayer awareness as an intervening variable. The sampling method used multi-stage sampling, the first stage was cluster random sampling and the second stage was proportional purposive sampling to obtain 115 respondents registered at the Klaten Pratama Tax Service Office. The analytical method used in this research is descriptive analysis, validity test, reliability test, correlation coefficient, coefficient of determination, regression analysis with the help of SPSS version 25 data processing and the Sobel test to analyze the influence of mediating variables. The results of the research show that the variables of tax sanctions, tax knowledge have a significant positive effect on taxpayer compliance and taxpayer awareness. Meanwhile, the tax socialization variable has no significant effect on tax compliance and taxpayer awareness. And the taxpayer awareness variable is not significant in mediating tax socialization and tax knowledge, while the taxpayer awareness variable has a significant effect in mediating taxpayer compliance. Kata Kunci: Tax socialization, tax sanctions, tax knowledge on taxpayer com-pliance through taxpayer awareness, tax socialization, tax sanctions, tax knowledge.